Tourism Village Development Strategy Through The Community Based Tourism Concept In Ciliang Village, Parigi District, Pangandaran Regency - Jauhari, Regitha; Novianti, Evi; Endyana, Cipta (International Journal of Science and Society, 2024)
Ciliang Village has tourism potential, namely nature, culture, and cuisine. One of the famous there is Batu Hiu Beach. However, this potential has not been explored optimally, as can be seen from the status of the developing village index in 2022 which still has the title "Developing". This research was conducted to identify the potential of the Ciliang Village area and determine a strategy for developing a potential tourist attraction. This research was conducted in the Ciliang Village Tourism Area, Parigi District, Pangandaran Regency. Data collection was carried out through interviews and observations then supported by the results of the documentation. Data and information are described descriptively. Based on the results of field observations and in-depth interviews, the strategy for developing tourist attractions by implementing the CBT concept can be started by conducting counseling and introducing the CBT concept, its benefits, and its impacts. This counseling can begin to be socialized to the closest stakeholders such as Pokdarwis and will then be disseminated to the surrounding community. Hopefully, with this development strategy, the Batu Hiu Beach tourist area can increase tourist visits.